Spatial Anatomy of Crime and Punishment from Forensic Architecture to Prison Architecture - Dokgöz, Deniz (The Bulletin of Legal Medicine, 2022)
It is possible to read the relationship between the crime and punishment with the spatial organization in historical continuity. Especially, the domination of punishment practices over space revealed the evolution of the spatial response of punishing in the historical process. As a part of the social discipline, the organization and the typology of confinement place has paved the way for the change and development of the building typologies produced in architectural sense. However, the studies carried out on the architectural practices of the place, where the crime was committed, point out to the year of 2010 at the earliest, and the production of space with new methods on this area shows that a new branch has emerged, forensic architecture. At this point, this study deal with the importance of integrating the fictional situation of the space by considering the notions of crime, punishment and castigating from forensic architecture to prison architecture.